Aplikasi Panduan Pramuka Berbasis Android - Alfa Wiani, Irenia; Hastuty, Ade; Sahidin, Sudirman; Masnur, Masnur (JURNAL UNITEK, 2025)
The utilization of digital technology in non-formal education has become an important strategy to enhance the effectiveness of learning, including in scouting activities. This research aims to evaluate the Android-based Scout Guide Application from three main aspects, namely the quality of the user interface, technical performance, and its benefits in supporting scouting learning. The research method used is descriptive quantitative with instruments in the form of closed questionnaires. A total of 30 respondents, who are active participants in scouting activities, were involved in this study. The data were analyzed using descriptive statistics through calculations of the mean, standard deviation, and frequency distribution. The research results show that the majority of respondents gave positive evaluations of the app’s interface design, which they found attractive, informative, and easy to use. The application also demonstrated stable technical performance with quick responses and relevant, useful features, such as semaphore videos and knot-tying simulations. Furthermore, the application is considered capable of enhancing the understanding of scouting materials in a visual and interactive manner. In conclusion, this application has great potential for integration into digital-based scouting learning activities. Further development is recommended to refine features and expand user reach. These findings contribute to innovations in scouting learning media in the era of digital transformation.